2019
DOI: 10.1093/cid/ciz222
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Antibiotic-resistant, Poly-microbial Bone Infection With Bacteriophages and Antibiotics Combination

Abstract: A patient with a trauma-related left tibial infection associated with extensively drug-resistant Acinetobacter baumannii and multidrug-resistant Klebsiella pneumoniae was treated with bacteriophages and antibiotics. There was rapid tissue healing and positive culture eradication. As a result, the patient’s leg did not have to be amputated and he is undergoing rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
117
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(135 citation statements)
references
References 11 publications
1
117
0
3
Order By: Relevance
“…Other recent clinical experience that exhibited positive outcomes with phage‐antibiotic combinations were described in another cystic fibrosis case, lung transplant patients, polymicrobial osteomyelitis, and others …”
Section: Review Of Positive Interactions Between Phage‐antibiotic Commentioning
confidence: 79%
“…Other recent clinical experience that exhibited positive outcomes with phage‐antibiotic combinations were described in another cystic fibrosis case, lung transplant patients, polymicrobial osteomyelitis, and others …”
Section: Review Of Positive Interactions Between Phage‐antibiotic Commentioning
confidence: 79%
“…36 The superiority of phage and antibiotic combination treatment to monotherapy of either has been reported, commonly with rifampin, implying a potential synergistic effect. 35,[37][38][39][40] In vivo, phage has also shown significant clearance of soft tissue infections. 41,42 In one abscess study, 10 9 PFU of bacteriophage M Sa eradicated infection in 97% of mice, when treated immediately after inoculation of 10 8 CFU of S. aureus intravenously.…”
Section: Bacteriophagesmentioning
confidence: 99%
“…A recent systematic review has concluded that phage therapy is effective and safe based on the limited publications to date, but more data are needed as challenges in manufacturing and the regulatory process remain. 147,148 Ultimately, all of these therapies need to overcome several obstacles not limited to optimal dosing and delivery and high-quality human trials of safety and comparative effectiveness before they can be incorporated into routine care limiting their current role in clinical practice.…”
Section: Inhaled Antibioticsmentioning
confidence: 99%